Information and Service Delivery : Case Studies from Kenya and Ethiopia - Kpundeh, Sahr; Khadiagala, Gilbert; Chowdhury, Shyamal (World Bank, Washington, DC, 2017)
This monograph probes the role of information in service delivery by focusing on key sectors in Kenya and Ethiopia. Findings from comparative studies done in 2005-06 in the health, education, and water and sanitation sectors plus public and private partnerships (PPPs) illustrate the significance of information access to delivery of quality services. Linking information access to service delivery is instructive to deepen institutional reforms around transparency and governance. This volume contends that three constraints-governance, trust, and technology deficits-impede information flows for service delivery in Ethiopia and Kenya. Although these constraints are formidable, the cases reveal that reforms in the governance arena have began to make a difference in the domain of service delivery. Using local researchers for this study has contributed to the World Bank's vision and mission of strengthening knowledge production by local institutions, particularly in Africa, where the low rate of the input of indigenous voices in the development debates is a growing concern. Augmenting the corpus of knowledge about African issues by Africans also fits into the objective of capacity building: providing local experts the opportunities to research and highlight experiences on the ground. As more countries embark on public sector reforms that deepen transparent information mechanisms and better service delivery, the need for more of these studies will increase. What the authors of this study have articulated is a rich research agenda that ties information access and service provision-research that should help advance policy dialogue with actors involved in public sector and governance reforms.